Analysis of Strength Factors of Steel Cord Conveyor Belt Splices Based on the FEM - Xianguo Li; Xinyu Long; Zhenqian Shen; Changyun Miao (Advances in Materials Science and Engineering)
Conveyor belt is an important element of the conveyor. The strength of the steel cord conveyor belt largely determines the carrying capacity, and it also has a great impact on operational safety. In this paper, the effect of different factors on the strength of the steel cord conveyor belt splices was studied. The FEM was used for simulation analysis, and the corresponding tensile experiments were carried out to verify. Steel cords of different lengths were simulated, and the simulation results agree well with the experimental results. On this basis, the steel cord length, steel cord diameter, rubber thickness, and different number of steel cords were investigated to study the effect on the pullout force of the steel cord conveyor belt splice. The numerical simulation results show that different steel cord diameters have more significant effect on the strength of the conveyor belt splice compared to rubber. The steel cord length and steel cord diameter impact on the steel cord conveyor belt is approximately linear. For the different number of the steel cords, the increase in the number of steel cords does not mean that the tension will increase by the same multiple, and the increase in pullout force is less than the increase in the number of steel cords. It provides guidance for the production of steel cord conveyor belts.